Mapping of the AgWp1 gene for the white petiole in celery (Apium graveolens L.). (February 2023) - Cheng, Qing; He, Yujiao; Lu, Qiaohua; Wang, Haoran; Liu, Sujun; Liu, Jinkui; Liu, Mengmeng; Zhang, Yingxue; Wang, Yihao; Sun, Liang; Shen, Huolin
Abstract: Celery ( Apium graveolens L.) is one of the most popular leafy vegetables worldwide. The main edible parts of celery are the leaf blade and especially the petiole, which typically has a white, green and red color. To date, there are very few reports about the inheritance and gene cloning of celery petiole color. In this study, bulked segregant analysis-sequencing (BSA-Seq) and fine mapping were conducted to delimit the white petiole ( wp1 ) loci into a 668.5-kb region on Chr04. In this region, AgWp1 is a homolog of a DAG protein in Antirrhinum majus and a MORF9 protein in Arabidopsis, and both proteins are involved in chloroplast development. Sequencing alignment shows that there is a 27-bp insertion in the 3′-utr region in AgWp1 in the white petiole . Gene expression analysis indicated that the expression level of AgWp1 in the green petiole was much higher than that in the white petiole. Further cosegregation revealed that the 27-bp insertion was completely cosegregated with the petiole color in 45 observed celery varieties. Therefore, AgWp1 was considered to be the candidate gene controlling the white petiole in celery. Our results could not only improve the efficiency and accuracy of celery breeding but also help in understanding the mechanism of chlorophyll synthesis and chloroplast development in celery. Highlights: Identification of a white petiole gene– AgWp1 . AgWp1 is a homolog of a DAG protein in Antirrhinum majus and a MORF9 protein in Arabidopsis. Marker Indel-21 can be improved the efficiency and accuracy of hybrid seed production in celery.